An Interactive Mobile Augmented Reality for Tourism Objects at Purbalingga District - Imam Tahyudin; Dhanar Intan Surya Saputra; Haviluddin Haviluddin (Institute of Advanced Engineering and Science, 2015)
This paper presents the development of an interactive mobile Augmented Reality (AR) for tourism promotion with eXtreme programming (XP) at Purbalingga district, Central Java that has many places of tourist attractions such as Owabong, Purbasari Pancuran Mas, Sanggaluri Park and Buper Munjuluhur. By applying the AR concept it is expected the tourism objects could be enhanced by augmenting the virtual brochures which could be viewed over a mobile device. In this study, mobile device Android platform is used to display interactive brochures of tourism promotion containing 3D models, animations, and sounds. The brochure will provide information in of real attractions of the tourism objects in the Purbalingga district.